Vaccination for Coronavirus Disease 2019 (COVID‐19) and Relationship to Osteoporosis Care: Current Evidence and Suggested Approaches. (14th April 2021) - Tsourdi, Elena; Yu, Elaine W.; Jan de Beur, Suzanne M.; Drake, Matthew T.
ABSTRACT: The development of coronavirus disease 2019 (COVID‐19) vaccines has proceeded at an unprecedented pace, with numerous trials conducted simultaneously across the world as a result of massive technological and financial resource expenditures. With multiple vaccines having now received regulatory approval, public health efforts to promote widespread vaccine dissemination are currently underway. There has been particular emphasis placed on vaccination of older populations, the age group in which COVID‐19 infection has been most lethal. However, such widespread vaccination approaches have necessarily raised important questions related to potential interactions with underlying diseases and concomitant treatments among persons to be vaccinated. Osteoporosis is a chronic condition marked by reduced bone strength and an associated increased risk for fracture that generally requires sustained medical intervention(s). Osteoporosis is neither associated with a higher risk of COVID‐19 infection nor by more pronounced disease severity following infection, such that individuals with osteoporosis need not be more highly prioritized for COVID‐19 vaccination. Osteoporosis therapies do not interfere with the efficacy or side effect profiles of COVID‐19 vaccines and should not be stopped or indefinitely delayed because of vaccination. Depending on the specific drug profile within an anti‐osteoporosis medication category, minor adjustments to the timing of drug administration may be considered with respect to the patient's COVID‐19 vaccination schedule. Herein we provide practical recommendations for the care of patients requiring treatment for osteoporosis in the setting of COVID‐19 vaccination. © 2021 American Society for Bone and Mineral Research (ASBMR).